(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
The mechanism of human colour perception is very complex and difficult to analyse, especially the neural mechanisms which are not well understood. In order to analyse the mechanism, it is essential to derive some quantitative visual scales. Therefore, an attempt has been made to analyse the colorimetric characteristics of the scales in CIELAB colour space and then obtain a colour description map using perceptual axes. In addition, the relationship between the many colour word pairs has been determined using descriptive scales and statistical analysis.With the results, we derived empirical colour emotion equations to express our impression induced from colour. The instrumental colorimetric assessment of colour emotions can be made through the colour emotion equations that were derived. With sensory database and colour emotion equations, we envisaged the development of some useful tools for Information Technology. Colour emotion scales obtained can be transformed to CIELCh, CIELAB, XYZ, and RGB values, which can be output as colours by display devices. This colour output can be used by applications such as product design and development.